Perancangan Art Gallery Untuk Anak Berkebutuhan Khusus (abk) Di Kota Bandung Dengan Pendekatan Desain Inklusi - Dhiya’ Ulhaq Salsabil, Annida; Cardiah, Tita; Septony Siregar, Fernando (eProceedings of Art & Design, 2024)
Children with special needs (ABK) are children who experience significant abnormalities or deviations, physically, mentally-intellectually, socially and emotionally in the process of growth and development compared to other children their age. This condition makes them need special education(Leli Erawati dkk., 2016). Based on the Bandung City Statistics Agency in 2022, there were 9,020 people with disabilities in Bandung City with disorders such as physical, visual, hearing, mental and other disabilities. Behind the shortcomings they have, there is also the ability to work like other children. Art therapy is one of the most popular and in-demand therapies. With art therapy, they can express themselves more through art. The works that have been made will be exhibited in the Art Gallery. Different from other exhibitions, the design of this Art Gallery is expected to be more friendly to children with special needs. With the hope that this Art Gallery can equalize opportunities in the gallery in enjoying art. The approach used is an inclusive design approach with the hope of meeting the needs of Art Gallery users who come from various types of visitors, as well as equalizing user activities and behavior in terms of facilities, accessibility, and interior. Keywords: children with special needs, art, art gallery, inclusive design